Scaffold-assisted Breast Augmentation: Approaching New Horizon by Three-Dimensionally Printed Personalized Tissue Regenerative Implants - Mohamed Lotfy Hamed, MD, MSc (Plastic and Reconstructive Surgery, Global Open)
Summary:. Current breast augmentation options face limitations and potential associated complications. Implant-based augmentation introduces risks such as capsular contracture and malpositioning, whereas fat grafting poses issues such as induration and infections, necessitating revisions. Tissue engineering, integrating 3-dimensional (3D) printing and biomaterials science, aims to overcome these challenges. However, the clinical translation of these advancements remains challenging, with many approaches falling short in demonstrating the necessary volume regeneration. A 28-year-old yoga instructor with a disinterest in traditional options sought an alternative solution. Custom-made biocompatible thermoplastic copolyester implants were proposed, approved, and implemented. Our approach utilized artificial intelligence, magnetic resonance imaging, computer-aided design, and lattice structure engineering for customizing the implant design. Three-dimensional printing and plasma technology surface treatment created implants of 300 and 315 cm3 volumes, weighting around 33 g with biomimetic properties. Implants were placed in the subglandular plane; an 8-month follow-up revealed well-maintained implants without complications, except for a conservatively managed hematoma, and excellent cosmetic outcomes. Magnetic resonance imaging analysis revealed revascularization and new tissue formation within the implant, demonstrating tissue integration without complications. The study addresses biomechanical issues and foreign body reactions that cause capsular contracture in breast augmentation and proposes a novel 3D-printed implant with ultralight weight, tissue integrative porous structure, and biomimetic environments for scaffold-guided tissue regeneration. In conclusion, the presented solution shows promise in overcoming current breast augmentation limitations, demonstrating safety, biocompatibility, and patient satisfaction. Further adoption and long-term studies with larger cohorts are needed to validate its clinical effectiveness and feasibility.